RdsA Is a Global Regulator That Controls Cell Shape and Division in Rhizobium etli - Martínez-Absalón, Sofía; Guadarrama, Carmen; Dávalos, Araceli; Romero, David (Frontiers in Microbiology, 2022)
Unlike other bacteria, cell growth in rhizobiales is unipolar and asymmetric. The regulation of cell division, and its coordination with metabolic processes is an active field of research. In Rhizobium etli, gene RHE_PE00024, located in a secondary chromosome, is essential for growth. This gene encodes a predicted hybrid histidine kinase sensor protein, participating in a, as yet undescribed, two-component signaling system. In this work, we show that a conditional knockdown mutant (cKD24) in RHE_PE00024 (hereby referred as rdsA, after rhizobium division and shape) generates a striking phenotype, where nearly 64% of the cells present a round shape, with stochastic and uncoordinated cell division. For rod-shaped cells, a large fraction (12 to 29%, depending on their origin) present growth from the old pole, a sector that is normally inactive for growth in a wild-type cell. A fraction of the cells (1 to 3%) showed also multiple ectopic polar growths. Homodimerization of RdsA appears to be required for normal function. RNAseq analysis of mutant cKD24 reveals global changes, with downregulated genes in at least five biological processes: cell division, wall biogenesis, respiration, translation, and motility. These modifications may affect proper structuring of the divisome, as well as peptidoglycan synthesis. Together, these results indicate that the hybrid histidine kinase RdsA is an essential global regulator influencing cell division and cell shape in R. etli.